Management of clubfoot by JESS : (Joshi's External Stabilization System) - Joshi, BB; Prabhoo, Ram; Kanaji, BG; Kaushik, Sandhya (New Delhi, India : Jaypee Brothers Medical Publishers, 2010)
Joshi's external stabilization system (JESS) application for CTEV evolved when Dr BB Joshi extended this as a special frame for clubfoot deformity. This technique is now globally acknowledged. Over 300 courses and worksshops have been conducted in various parts of the country, with national and international participation. Over the last 20 years, since its development, many lectures and orations on this subject have been presented. Prime centers all over the country are evolving with their own experience in the form of postgraduate dissertations for MS and MCh courses and presentations at orthopedic and plastic surgical scientific forums. This technique allows simultaneous corrections of all three components of the clubfoot deformity. Ideal technique for severe deformity correction not amendable to conservative treatment, neglected, recurrent and resistant clubfoot. This book useful for postgraduate students, orthopedic surgeons, students of rural surgery and practitioners.
1. Classification and Evaluation of Clubfoot MC Vaishnav, Ram Prabhoo, BG Kanaji 2. Joshi's Method of Conservative Management in Neonates BB Joshi, BG Kanaji 3. Correction of CTEV by Controlled Differential Fractional Distraction Using JESS BB Joshi, BG Kanaji, Ram Prabhoo, Aditya Kaushik 4. Causes of Failure or Relapse of Clubfoot BB Joshi 5. Dynamic Splinting for Residual Deformities and Early Recurrence BB Joshi, Mukesh M Doshi 6. Rehabilitative Exercises BB Joshi 7. Comments and Frequently Asked Questions (FAQs) BB Joshi, VM Iyer Further Reading
Incluye contenido
Incluye index
Keywords: PIE EQUINOVARO; CLUBFOOT